General Practitioners' preferences and use of educational media: a German perspective - Rieger Monika A; Vollmar Horst; Butzlaff Martin E; Ostermann Thomas (BMC, 2009)
Abstract Background Several studies suggest that General Practitioners (GPs) prefer "traditional" media such as journals or quality circles when they are seeking out different options to meet their continuing medical education (CME) requirements. A survey was designed in order to gain a better understanding of German General Practitioners' preferences for different forms of educational media that will meet their CME needs. Methods Four hundred and forty nine (N = 449) German physicians were contacted to take part in this study on the occasion of one of their quality circle meetings. The participating physicians received a standardized 26-item-questionnaire that surveyed their preferences for different forms of educational media. A factor analysis was performed in order to determine whether the observed variables can be explained largely or entirely in terms of the underlying patterns. Results Two hundred and sixty-four physicians with an average age of 51.1 years participated (28.5% female, 71.5% male). We found that GPs favor learning environments such as: journals, colleagues, and quality circles. New media like the internet was used less often for their learning activities, even though the usage of the internet in general was quite high. The most important requirements for media in medical education as perceived by the participants were its relevancy for daily practice and dependability. Conclusion Despite a growing use of the Internet it seems that German GPs favor "classical/traditional" settings for their learning activities. These results should be taken into consideration when planning CME or CPD programs or other learning activities. Trial registration Current Controlled Trials ISRCTN36550981.